Extended Approach of Visual Secret Sharing for Digital Images (International Journal of Engineering and Computer Science, 2015)
In visual secret sharing (VSS) secret image is encrypted in shares, with each participant involved in technique holding one or more shares, all the shares are required to reveal any information. The shares may appear as noise like pictures and will arouse suspicion and increase interception risk during transmission. Thus VSS scheme suffer from a transmission risk. With increasing number of shares, it becomes more difficult to manage the share. The proposed scheme shared secret image by generating only two noise-like color shares using natural image. These noise-like color shares are hided in two cover images to increase the security level